Farmers’ Perception and Adaptation to Climate Variability in Nandi County, Kenya - S. K., Omasaki; A. N., Mokoro (African Journal of Education,Science and Technology (AJEST), 2023)
Climate variability impacts environment social and economic growth. Much of these effects are felt by smallholder farmers whose livelihoods depend on natural resources. However, smallholder farmers have limited knowledge to link anticipated climate variability impacts at the local levels. In this study, farmers’ perception and level of awareness about climate variability and how it impacts smallholder dairy farming was analyzed. A total of 350 smallholder dairy farmers from eight sub-locations of Aldai Sub-County, Nandi County, Kenya were interviewed and compared farmer’s perceptions about climate variability with trends from Meteorological Data. Analysis was done using a multivariate Probit regression model. Results showed that, on average, temperatures were rising, and this rise was more prominent during the short rainy seasons. Given the rising trends in temperature, the respondents above 50 years were asked to compare the current weather conditions with those observed in the last 32 years ago (i.e., from January 1980 to December 2012) as a way of measuring their perception about climate variability. The majority (70%) of smallholder farmers identified drastic changes in temperature patterns. Only 38.12% with at least one year of farming experience were able to note the rise in temperature levels. These results indicate that smallholder farmers who are considered to have limited information about climate variability were more likely to perceive changes in weather patterns. In conclusion, we found that access to extension services, type of land tenure, and access to credit facilities are important in enhancing the adaptive capacity of farmers.